PENGARUH MARGIN LABA KOTOR, STRUKTUR AKTIVA, TOTAL ASSET TURNOVER DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN LOGAM DAN SEJENISNYA - Agustina Sinaga, Rifka; Vonida Hutajulu, Enzelina Septiani; Ompusunggu, Tuty; Purba, Eko Sanjaya; Dini, Siti (Aksara Public, 2019)
This research aims to determine the influence of variables of the gross profit margin, asset structure, total asset turnover and the company's size to the capital structure at IDX in 2012-2016. This research sample obtained 16 companies that selected as many as 7 companies that meet the criteria by using purposive sampling with certain criteria. The type of data used in this research is quantitative data. The data source in this study is secondary data. Data collection techniques are carried out with documentation techniques and data analysis using multiple linear analysis with the help of Sofftware SPSS 25. The results of a partial study (T) indicate that gross profit margins are negatively and insignificant to the metal structures in metals companies and the like in IDX, the asset structure and size of the company have a positive and significant effect to the capital structure. While the total asset turnover is positive and insignificant to the company's capital structure and the like in IDX. The simultaneous research result (F) shows the gross profit margin, asset structure, total asset turnover and the influential and significant company size of the capital structure.